Features of the discipline knowledge network: evidence from China - Shan, Wei; Liu, Chen; Yu, Jing (Technological and Economic Development of Economy, 2014)
Interdisciplinary knowledge exchange constitutes a network with discipline nodes and knowledge flow edges. Using data on Chinese academic literature, the current paper establishes a discipline knowledge network and analyses its structural features. Citation analysis is first used to measure the flow of knowledge between disciplines to build a discipline knowledge network. Subsequently, the features of the network, such as degree distribution, degree correlation, knowledge flow mode and other structure properties, are then analysed based on complex networks and social network theory. The tail of the degree distribution of this discipline knowledge network is in concordance with exponential distribution. The network has also a distinct hierarchical structure. Moreover, the knowledge flow between disciplines is directional. It flows from certain basic and academic disciplines to the applied disciplines. First published online: 28 Jan 2014